The impact of smartphone use and social networks on attention, memory and anxiety of university students: an integrative review (Research, Society and Development, 2022)
Through the accelerated advancement of technologies, through the constant consumption of increasingly modern smartphones, whether of the most diverse models, containing the most varied applications, including facebook, whatsapp, twitter and instagram with their respective functionalities, this work has the purpose of to analyze the effects of smartphone use and social networks on the attention, memory and anxiety of university students. Thus, an integrative literature review was carried out in which national and international articles from the last five years were selected from the following databases: PubMed (database developed by the National Library of Medicine), Lilacs (Latin American and Caribbean Literature on Health Sciences) and Scielo (Scientific Electronic Library Online). With the use of these descriptors, namely: (smartphones OR smartphone OR cell phone OR cell phones OR social networks OR facebook OR instagram OR whatsapp OR twitter) AND (“psychological processes” OR attention OR memory OR anxiety) AND (youth OR young OR teenager OR adolescents OR students OR students OR university students), 537 articles were found. When applying the exclusion criteria, 12 articles remained for analysis. Most of the results showed a statistically significant association of smartphone and social media use with anxiety and also with other variables such as depression and stress. No articles were found that addressed the relationship between the use of smartphones and/or social networks with memory and attention. This literature review, by summarizing the main findings on the topic, may be useful for future interventions and research.